Facilitator management system for campus orientation programme - Mahamad Zakaria, Muhammad Luqman; Samsudin, Noor Azah; Mohamed, Rozlini; Mustapha, Aida (Penerbit UTHM, 2017)
Campus Orientation Programme (COP) designed for higher education institution aims to provide students with knowledge and skills that will assist them in making a smooth transition to university life (Benavides & Keyes, 2014). The COP conducted at University Tun Hussein Onn Malaysia (UTHM) is preparing new students with knowledge and skills to survive in academic, personal management, and social life in higher education environment. Indeed, the COP takes the opportunity to introduce to the new students a wide range of activities such as ‘starting school’ session, academic briefing, and college events. The activities are planned and carried out by the Student Affairs Office (SAO) staff and college residence fellow. Besides that, SAO also recruits senior students to become facilitators to aid the running of students’ activities throughout the COP week. However, the 74 Selected Topics In Information Technology existing procedures directly related to managing the facilitators are carried out manually: